Intake Ground Vortex Prediction Methods - Murphy, J. P.; MacManus, David G. (AIAA, 2011)
For an aircraft turbofan engine in ground operations or during the take-off run a ground vortex can occur which is ingested and could potentially adversely affect the engine performance and operation. The vortex characteristics depend on the ground clearance, intake flow capture ratio and the relative wind vector. It is a complex flow for which there is currently very little appropriate quantitative preliminary design information. These aspects are addressed in this work where a range of models are developed to provide a method for estimating the key metrics such as the formation boundary and the ground vortex size and strength. Three techniques are presented which utilize empirical, analytical and semi-empirical approaches. The empirical methods are primarily based on a large dataset of model-scale experiments which quantitatively measured the ground vortex characteristics for a wide range of configurations. These include the effects of intake ground clearance, approaching boundary layer thickness, intake Mach number and capture velocity ratio. Overall the models are able to predict some of the key measured behaviours such as the velocity ratio for maximum vortex strength. With increasing empiricism for key sub-elements of the model construction, an increasing level of agreement is found with the experimental results. Overall the three techniques provide a relatively quick and easy method in establishing the important vortex characteristics for a given headwind configuration which is of significant use from a practical engineering perspective.